Reliability and validity of a Turkish version of the acceptance and action diabetes questionnaire - Karadere, Mehmet Emrah; Yavuz, Kaasım Fatih; Yazla Asafov, Ece; Küçükler, Ferit Kerim (Korean Neuropsychiatric Association, 2019)
Objective The aim of this study is to perform validity and reliability examination of the Turkish form of Acceptance and Action Diabetes Questionnaire, and to investigate whether this scale is a measurement tool for evaluation of psychological flexibility levels in a sample of patients with diabetes in Turkey. Methods This study was conducted with 105 patients. Turkish forms of the Beck Depression Inventory (BDI), Problem Areas in Diabetes Questionnaire (PAID), State-Trait Anxiety Inventory (STAI-I and STAI-I I), Audit of Diabetes-Dependent Quality of Life (ADDQoL) and Turkish form of Acceptance and Action Diabetes Questionnaire (TAADQ) were applied. SPSS 20.0 and AMOS was used in statistical analysis. Results 56.12% of the patients were female and the mean of age was 54 (SD=+/- 9.9) years. The mean duration of education was found 7.65 (SD=3.97) years. 74.8% of the patients most of whom (83.3%, n=85) had diabetes mellitus and the mean glycemic control calculated with HbAlc was 8.02 +/- 1.91. According to the final fit indices, we found that the revised and corrected 9-item model was superior over the previous model. Cronbach Alpha coefficient of TAADQ was found as 0.836. Conclusion TAAI)Q is a valid and reliable assessment tool in Turkish population. So TAADQ will be a powerfull tool in assessing psychological flexibility in diabetes patients.
WOS: 000472919500002
PubMed ID: 31247700
Keywords: Acceptance and Action; Diabetes; Reliability and Validity; Turkish Version